Marine bacterium Seonamhaeicola algicola strain CC1 as a potential source for the antioxidant carotenoid, zeaxanthin - Tatas Hardo Panintingjati Brotosudarmo; Edi Setiyono; Koichiro Awai; Delianis Pringgenies (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Currently, there are only six species in the genus Seonamhaeicola, i.e., Seonamhaeicola aphaedonensis, S. algicola, S. marinus, S. acroporae, S. maritimus, and S. sediminis. These bacteria have typical yellow or orange color. Among the identified strains, only S. marinus that had been reported to have a yellow polyene flexirubin pigment. However, the presence of carotenoid pigments has not been reported in this genus. Recently, we successfully isolated a new strain, S. algicola strain CC1, bacterium that was found in association with a red seaweed, Halymenia sp., collected from the coast of South Malang, Indonesia. The strain was grown well in the Zobell marine agar 2216E producing yellowish pigments. According to the 16S rRNA sequencing analysis and BLAST search, the strain is closely related to S. algicola strain Gy8, with 99.78% identity. The pigment composition was separated and analyzed by a high-performance liquid chromatography with tandem mass spectrometry detection (HPLC-MS/MS) and the strain was found to produce zeaxanthin as the major component, which appeared at a retention time (tR) of 28.89 min, showing a typical mass spectrum with a molecular ion at m/z 568.5 [M]+ and four product ions at m/z 261.4 [M−307]+, 476.6 [M−92]+, 429.3 [M−139]+, and 536.5 [M− 32]+. Other carotenoids, including zeaxanthin cis isomers, β-cryptoxanthin, β-carotene cis isomer, and β-carotene, are as minor components. The novel and noteworthy finding of this report is the identification of a Seonamhaeicola species that produces carotenoids and can be used as a source of zeaxanthin.